Innovation Model of China's High-End Equipment Industry: Do Social Capital and Dynamic Capabilities Matter for the COVID-19 Crisis? - Ai, Yuhong; Peng, Diyun (Frontiers in Public Health, 2021)
This paper explores the different model combinations of enterprise innovation in China based on the roles of social capital and dynamic capabilities. We implement the Qualitative Comparative Analysis to understand the nonlinear asymmetric relationships better. We use the data of 44 Listed Companies in China's high-end equipment manufacturing industry data and find that two innovation models (market-oriented independent innovation and industry-supported learning innovation models) are valid. Social capital, dynamic capabilities, and intra-industry networks are the main determinants of these innovation models. We also discuss the implications on the Chinese enterprises' innovation dynamics to sustain the economy's high-quality development, including the COVID-19 crisis era.